2015
DOI: 10.1021/acs.est.5b00887
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Sustainability of Non-Networked Sanitation Technologies: An Approach to Standardization

Abstract: Non-networked sanitation technologies use no sewer, water or electricity lines. Based on a review of 45 commercially distributed technologies, 12 (representing three concepts) were selected for a detailed audit. They were located in six countries of Africa and Asia. The safety of users was generally assured and the costs per use were not excessive, whereas costs were fully transparent for only one technology surveyed. A main drawback was insufficient quality of the byproducts from on-site treatment, making rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Hence, the main contribution of this book is to provide such a framework (or model) known as the regenerative sanitation framework, which is not technocentric and toilet-latrine-focused but where all key critical aspects of sanitation subsystems, dimensions and components are interlinked for total rejuvenation and revitalization of the whole spectrum of sanitation management systems as well as for the development and implementation of innovative solutions. Providing comprehensive sanitation solutions for the current global challenges depends not only on availability of technology, but also on many other factors like management of sanitation delivery, quality of institutions that manage them, prevailing psycho-socio-cultural, economic and ecological conditions that influence sanitation planning, technology design and development, management processes and practice, as well as financial and governance mechanisms (Starkl et al, 2015;Tilley et al, 2014a;Zurbrugg & Tilley, 2009). Sanitation in this book is used to mean the systemic integration of measures for managing human waste in a safe and resourceful pattern adapted to fit specific and peculiar contexts (Box 1.5).…”
Section: Sanitation Conceptual Frameworkmentioning
confidence: 99%
“…Hence, the main contribution of this book is to provide such a framework (or model) known as the regenerative sanitation framework, which is not technocentric and toilet-latrine-focused but where all key critical aspects of sanitation subsystems, dimensions and components are interlinked for total rejuvenation and revitalization of the whole spectrum of sanitation management systems as well as for the development and implementation of innovative solutions. Providing comprehensive sanitation solutions for the current global challenges depends not only on availability of technology, but also on many other factors like management of sanitation delivery, quality of institutions that manage them, prevailing psycho-socio-cultural, economic and ecological conditions that influence sanitation planning, technology design and development, management processes and practice, as well as financial and governance mechanisms (Starkl et al, 2015;Tilley et al, 2014a;Zurbrugg & Tilley, 2009). Sanitation in this book is used to mean the systemic integration of measures for managing human waste in a safe and resourceful pattern adapted to fit specific and peculiar contexts (Box 1.5).…”
Section: Sanitation Conceptual Frameworkmentioning
confidence: 99%
“…This figure constitutes an average 0.9% of gross domestic product (GDP) of the Latin America, Caribbean, Africa and Asia Pacific countries impacted by poor sanitation, which is a modest decline from 1% GDP five years ago (LIXIL et al, 2016). Studies have shown that several sewerage systems globally discharge sewage without treatment and as a result more than 50% of the world's rivers, oceans and lakes are polluted with untreated wastewater; and on-site sanitation systems characterized by high rates of failure and absence of technological improvement rates, especially in the developing countries, add to this burden (Baum et al, 2013;Brown & Root, 2001;Cookey et al, 2016d;Jones et al, 2004;Siegrist et al, 2000;Starkl et al, 2013Starkl et al, , 2015. To eliminate the above challenges, sanitation technology and management solutions should be approached with the NToB principle and from localized pyscho-socio-cultural-economic, ecological, geographical, resource recovery and technology perspectives; and within the technology (Box 2.9)…”
Section: No-transfer-of-burden (Ntob)mentioning
confidence: 99%
“…(I) No policy and adequate institutional frameworks (Ekane et al, 2016;Elledge et al, 2002); (II) Poor implementation of policy, where it exists (Ekane et al, 2016;Seppälä, 2002); (III) Fragmentation and gaps in policy and institutional frameworks (Ekane et al, 2016;Morella et al, 2008); (IV) Poor prioritization of sanitation and hygiene (Ekane et al, 2014(Ekane et al, /2016ECA, 2012); (V) Implementation failures characterized by overemphasis on numbers of toilets rather than functionality, serviceability and reliability (Ekane et al, 2016;Kvarnström et al, 2011); (VI) Poor coordination of actors and activities (ECA, 2012;Ekane et al, 2014Ekane et al, /2016UN-Water, 2012); (VII) Overreliance on technological solutions with less emphasis on other subsystems and components of sanitation such as psycho-social-cultural-ecological and resource systems (Curtis et al, 2011;Ekane et al, 2016;Morella et al, 2008); and (VIII) Inadequate financial and technical capacities to drive meaningful change (Ekane et al, 2014(Ekane et al, /2016). (IX) Inadequate standards that support technological innovations, scalability and replicability (NOWRA, 2007;Starkl et al, 2015).…”
Section: Special Considerations For Sanitation Governancementioning
confidence: 99%